Tiliacora triandra extract and its major constituent attenuates diabetic kidney and testicular impairment by modulating redox imbalance and pro‐inflammatory responses in rats. (17th September 2020) - Song, Peng; Sun, Chen; Li, Jinbo; Long, Tong; Yan, Yixin; Qin, Hongping; Makinde, Emmanuel Ayobami; Famurewa, Ademola C; Jaisi, Amit; Nie, Ying; Olatunji, Opeyemi Joshua
Abstract: BACKGROUND: Literature has demonstrated that diabetes is associated with renal complication and testicular dysfunctions. The current study explored the potential of Tiliacora triandra extract and its major component against diabetic kidney and testicular damages in rats. METHODS: Diabetes was induced by high fat diet/streptozotocin (HFD/STZ) and treated orally with Tiliacora triandra extract (TTE, 100 and 400 mg kg −1 body weight) and its major component, 5, 7‐dihydroxy‐6‐oxoheptadecanoic acid (DHA, 25 mg kg −1 body weight) for 30 consecutive days. Testicular activities of testicular enzymes, serum levels of testosterone, luteinizing hormone (LH) and follicle‐stimulating hormone (FSH), sperm parameters and urinalysis for protein and albumin levels were evaluated. Renal and testicular biomarkers of oxidative stress and pro‐inflammation were analysed along with histology. RESULTS: The experimental diabetes induced significant alterations in the levels and activities of indices evaluated compared to non‐diabetic normal rats. The 28‐day treatment of diabetic rats with TTE and DHA markedly improved activities of testicular enzymes, restored levels of testosterone, LH and FSH and sperm parameters compared to untreated diabetic rats. TTE and DHA abrogated proteinuria and reversed urine albumin level. Testicular and renal oxidative stress and pro‐inflammation were attenuated in diabetic rats treated with TTE and DHA. The diabetes‐mediated histopathological damage was alleviated in the kidney and testis. CONCLUSION: The protective effect of TTE and DHA against diabetes induced kidney and testicular damages may be related to its antioxidant and anti‐inflammatory activities. © 2020 Society of Chemical Industry